MAC OS X digital media all in one - Ness, Robyn (Sams teach yourself all in one., 2003)
Digital Photos, Video, and Music All in One is designed to teach the new computer user how to easily work with a variety of digital media. It doesn't assume the reader wants to learn how to use just one product, but covers multiple products and technologies together in a logical fashion: Digital Cameras Photoshop Elements Burning CDs and DVDs Scanners and Printers MP3s and Digital Music Digital Videos.